Governing the Nexus Water, Soil and Waste Resources Considering Global Change - Kurian, Mathew; Ardakanian, Reza.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Based on papers and discussions surrounding the international kick-off workshop of the UNU-FLORES institute, held in Dresden, Germany in November, 2013, this book elaborates on key themes of the nexus approach to management of environmental resources- water, soil and waste. The first three chapters address issues of global change and the nexus approach to environmental governance. Discussion includes concepts of poverty-environment nexus, adapative management, questions surrounding inter-sectionality, interactionality and hybridity. Chapters 4, 5 and 6 elaborate on the challenges of financing infrastructure projects, including questions of accountability and autonomy, in the context of decentralization and deregulation. Issues relating to the role of central transfers, taxes and tariffs and potential applications of results-based financing approaches to support sustainable service are also discussed. Chapters 7, 8 and 9 explore strategies for implementation, focusing on European experience with application of life-cycle cost analysis in water and wastewater projects, the use of an agro-ecology framework to support wastewater reuse in agriculture and applications of data visualization techniques for evidence based decision making. The book concludes with a chapter by the editors, whose title expresses perhaps the most difficult question faced by development planners in addressing challenges of global change: Policy is Policy and Science is Science: Shall the Twain Ever Meet?
Part I Global Change and the Nexus Approach to Management of Environmental Resources -- 1. The Nexus Approach to Governance of Environmental Resources Considering Global Change -- 2. The Water-Energy-Food Nexus-Enhancing Adaptive Capacity to Complex Global Challenges -- 3. The Nexus Approach to Managing Water, Soil and Waste under Changing Climate and Growing Demands on Natural Resources -- Part II Financing of Infrastructure Projects: Implications for Sustainability and Accountability -- 4. Inter-Governmental Fiscal Relations: Questions of Accountability and Autonomy -- 5. Results Based Financing and its Potential Role in Advancing the Nexus Approach -- 6. Life-Cycle Cost Analysis of Infrastructure Projects -- Part III Strategies for Implementation: Guidance on Resource Reuse and Data Visualization -- 7. Applications of Life-Cycle Cost Analysis in Water and Wastewater Projects: Lessons from European Experience -- 8. Designing Sustainable Reuse Systems: Towards an Agroecology of Wastewater Irrigation -- 9. Data Visualization of Water Services: Applications for Nexus Governance in Africa -- 10. Policy is Policy and Science is Science: Shall the Twain Ever Meet?. .
Keywords: Sustainable development; Environment; Remote sensing; Agriculture; System theory; Sustainable Development; Environment, general; Remote Sensing/Photogrammetry.; Agriculture; Complex Systems